Influence of thermal exposure on the microstructure evolution and mechanical behaviors of an Al-Cu-Li alloy. (March 2023) - Wu, Mingdong; Liu, Wensheng; Xiao, Daihong; Huang, Lanping
Graphical abstract: Highlights: The T85 treated Al-Cu-Li alloy was systematically investigated under thermal exposure at 100–300 °C for up to 1000 h. The evolution of precipitation characteristics during thermal exposure was revealed. Fracture toughness was greatly affected by the morphology and distribution of grain boundary precipitates. The qualitative relationship between mechanical properties and multiscale microstructure was established. Abstract: In this study, the T85-treated Al-3.78Cu-1.17Li-0.7 Mg-0.32Ag-0.25Mn-0.33Zn-0.12Zr alloy thermally exposed at a series of temperatures (100–300 °C) for 100 h, 500 h, and 1000 h was systematically investigated. The results show that the thermal stability of the alloy is more closely correlated with thermal exposure temperature than with exposure duration. Excellent thermal stability in strength is obtained below 150 °C, which can be linked to the diameter and number density of T1 (Al2 CuLi) precipitates continually increasing with a thickness less than 2 nm. However, the widened precipitation-free zones (PFZs) associated with continuous grain boundary precipitates (GBPs) benefit intergranular fracture, contributing to a decrease in toughness and elongation. In the window of 175–200 °C, T1 precipitates tend to thicken and are gradually substituted by coarse θ′-Al2 Cu and S-Al2 CuMg with elevating temperature. Simultaneously, the continuous GBPs transverse to discrete circle-like shapes, and thus intergranular ductile fracture becomes dominant. Therefore, the related hardness and strength decrease, while the electrical conductivity and toughness are the opposite. At temperatures over 250 °C, thermal exposure can reduce the dislocation density and dissolve T1 phases to form T2-Al6 Cu(Li, Mg)3 and cubic C phases, leading to a dramatic decrease in strength and toughness.